An insight of Europeans’ knowledge about dietary fibers in relationship with obesity - Tarcea, Monica (2019)
Objectives: To estimate the relationship between socio-demographic characteristics of Romanian population, and their knowledge towards dietary fibre intake, the information sources preferred and perception of obesity related health risks. Methods: We used a convenient cross-sectional survey, and the data were collected using a validated questionnaire, disseminated online. Six different Romanian counties with 57 cities were selected in 2016, with 670 participants, and we used the SPSS program 22.0 for statistical purpose. The same questionnaire was applied in other 7 European countries, part of an international project design. Results: The knowledge about dietary fibres intake was low in Romanian sample, also was the ingestion of foods rich in fibre (fruits, vegetables and cereals). Compared to men, women agree significantly more frequent that fibres in appropriate amounts can prevent or treat diseases (U=44607, z=-4.66, p<0.001, r=0.18) and separately related to specific diseases, that fibres can prevent and/or treat cardio-vascular diseases, cholesterol, bowel cancer, breast cancer, constipation, and diabetes, but with no differences regarding the deficiency of vitamins and minerals (p=0.774) or obesity (p=0.399). Regarding the differences observed by countries, the highest fruit consumption was found for Portugal (11.7 portions per week), while the lowest was for Hungary (7.4) and Latvia (7.1). Turkey that had the highest interest for food labelling (4.0 points), contrarily to Macedonia (3.0) with the lowest value, and Hungary with 3.6 points. The indepth analysis of factors that are able to influence European’s knowledge and attitudes towards food fibres, defined the social profile of the respondents with interest on dietary fibre intake, which is: young females, with at least high school education, that considers internet and television like main sources of information regarding fibres. Conclusions: Based on our results, we can elaborate efficient community and school intervention programs, more focused on modern information technology and communication skills, fit to the consumer’s profile in order to promote a healthy nutrition behavior and proper knowledge.